The influence of heavy metals on human health and the occurrence of autism - Marković, Miroslav; Marković, Olivera (Education and Research in Health Sciences, 2026)
Food toxicology explains the ways of intake of toxins from food, distribution in the body, as well as metabolism and excretion. Toxins can occur naturally in food, arrive from the outside environment, but the human factor is also significant. Diagnostic criteria and screening, increased awareness of the wider professional and social public, as well as numerous defectological work methods have initiated a greater sensitivity for autism spectrum disorders (ASD). This overview of the presence of heavy metals in food talks about their toxicological properties and harm to human health. As the prevalence of the number of children on the autism spectrum is increasing, and the etiology is unknown, attention can also be drawn to the influence of heavy metals as external factors (which are ingested with food) on the occurence of this developmental disorder.